Interdependence of international capital markets - Suzana Baresa; Sinisa Bogdan; Zoran Ivanovic (UTMS Journal of Economics, 2014)
World financial centers have an impact on the economies around the world. This particularly applies for the US equity market. Transactions which are performed on the US market define market trends in most of the world's financial markets, the only question that arises "is to what extent". Purpose of this research is to define and quantify the relationship of the US capital markets, and market equity securities selected on world stock markets. This research will explain the concept of capital markets, its divisions and legislation. The research part is based on quantifying relationship of the US equity market index on the indices of the London Stock Exchange, the Tokyo Stock Exchange and the Zagreb Stock Exchange.
Keywords: G10; G15; 330; Capital Market; Zagreb stock exchange; stock market indices